Composition Design and Fatigue Curves of Hardfacing Materials for Cold Roll. (29th February 2016) - Chen, C. L.; Chen, C. X.; Guo, Z. H.; Ding, J.; Han, X.; Jiang, Q.
Abstract : In order to improve the fatigue life of cold rolls, a series of hardfacing alloys were designed by orthogonal experiments considering the interaction between carbon, chromium, and niobium. Hardfacing layers were produced by Tungsten Inert Gas (TIG) arc welding. The effects of alloy content on microstructure and carbides and fatigue behavior at different load frequency and different temperature were analyzed. The results show that suitable combination of 0.5% C, 4.0% Cr, and 2.0% Nb can obtain a high hardness of 54.7 HRC for the formation of fine lath martensite and carbides with dispersed distribution. The new designed hardfacing materials have similar Δ ε - N curves with parent material in low load frequency and below 400°C.